LEVELS OF MALONIC DIALDEHYDE AND SUPEROXIDE DISMUTASE IN CHILDREN FROM A ZONE WITH HEIGHTENED RADIATION BACKGROUND - Z.A. BADALOVA; J.S. DODKHOEV; A.M. SABUROVA (Avicenna Tajik State Medical University, 2019)
Objective: To study the content of superoxide dismutase (SOD) and malonic dialdehyde (MDA) in the blood of children by the influence of heightened radiation background. Methods: The levels of MDA and SOD in the blood were determined in 20 newborns and in 60 to 3-5 years old children living in the area of high radiation background. The control group included 80 children and newborns living in areas with a natural radiation background. The content of MDA was determined by the method of I.D. Stalnaya, and the level of SOD - by the method of reduction of nitro-blue tetrazole in serum. Results: Levels of MDA in children living in conditions with a natural radiation background, were: newborns - 0.065±0.003 μmol/l; 3 years old children - 0.073±0.003 μmol/l; children 4 years old - 0.065±0.003 μmol/l; children 5 years old - 0.060±0.002 μmol/l. At the same time, in children living in conditions of heightened radiation background, the level of MDA was higher, with the greatest level among newborns - 0.879±0.025 μmol/l. In children 3, 4 and 5 years, this values were 0.301±0.025; 0.338±0.027 and 0.671±0.049 μmol/l, accordingly. The content of SOD in children living in conditions with a normal natural radiation background was as follows: newborns - 12.7±0.2 c. u./l; children 3 years old - 13.1±0.1 c. u./l; children 4 years old - 13.4±0.1 c. u./l; children 5 years old - 13.1±0.1 c. u./l. At the same time, in children living in conditions of heightened radiation background, considerably low levels of SOD were detected: newborns - 11.5±0.2 c. u./l; children 3 years old - 11.7±0.1 c. u./l; children 4 years old - 11.5±0.1 c. u./l; children 5 years old - 11.5±0.1 c. u./l. Conclusion: The results of conducted research revealed the presence of oxidative stress and imbalance of the pro- and antioxidant systems in children living in conditions of heightened radiation background